SINGLE CHANNEL SEISMIC APPLICATION FOR GAS CHARGED SEDIMENT RECONNAISSANCE IN GEOHAZARD STUDY OF PORT CONSTRUCTION AT WETLAND AREA - Wiguna, Taufan; Moefti, Omar; Rahadian, Rahadian; Irfan, Muhamad (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2016)
Gas charged sediment as a one of parameter for geohazard study in infrastructure especially in swamp area. Instability of sediment layer for exampel subsidence and landslide result in geohazard potention that caused by gas charged sediment. Seismic single channel can be used to identufy gas charged sediment location. Seabed morphology is collected from bathymetry and tidal survey. From seismic profile interpretation shows gas charged sediment indication in Line A and Line B. That indication emerged by presence of acoustic turbid zone and acoustic blanking. Line A and Line B location will be spotlight in next geotechnic port construction study.Â